2020
DOI: 10.1038/s41419-020-2540-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SOX2OT promotes temozolomide resistance by elevating SOX2 expression via ALKBH5-mediated epigenetic regulation in glioblastoma

Abstract: Temozolomide (TMZ) resistance is a major cause of recurrence and poor prognosis in glioblastoma (GBM). Recently, increasing evidences suggested that long noncoding RNAs (LncRNAs) modulate GBM biological processes, especially in resistance to chemotherapy, but their role in TMZ chemoresistance has not been fully illuminated. Here, we found that LncRNA SOX2OT was increased in TMZ-resistant cells and recurrent GBM patient samples, and abnormal expression was correlated with high risk of relapse and poor prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…The MTA3/SOX2-OT/SOX2 axis has been involved as a prognostic factor for poor clinical outcomes in esophageal squamous cell carcinoma patients [40]. Results from our study confirm that overexpressed LncRNA SOX2-OT is involved in the control of SOX2-OT/SOX2/GLI-1 axis expression, as probable key archetypes, including as "scaffold" to RNA-binding protein (RBP) [65], and ceRNA function reported on SOX2-targeting miR200c [15], or hypothetically involved in ceRNA activity on miR326 [66], or miR218 [67] whose miRNAs are involved in GLI-1targeting. Some of these functional archetypes have been shown or suggested to participate in therapy resistance and clinical prognosis in lung cancer, as it has been previously reported [68].…”
Section: Similar Findings Have Been Reported In Laryngeal Squamous Cesupporting
confidence: 65%
“…The MTA3/SOX2-OT/SOX2 axis has been involved as a prognostic factor for poor clinical outcomes in esophageal squamous cell carcinoma patients [40]. Results from our study confirm that overexpressed LncRNA SOX2-OT is involved in the control of SOX2-OT/SOX2/GLI-1 axis expression, as probable key archetypes, including as "scaffold" to RNA-binding protein (RBP) [65], and ceRNA function reported on SOX2-targeting miR200c [15], or hypothetically involved in ceRNA activity on miR326 [66], or miR218 [67] whose miRNAs are involved in GLI-1targeting. Some of these functional archetypes have been shown or suggested to participate in therapy resistance and clinical prognosis in lung cancer, as it has been previously reported [68].…”
Section: Similar Findings Have Been Reported In Laryngeal Squamous Cesupporting
confidence: 65%
“…Furthermore, the mechanism of balance between canonical and noncanonical Wnt signaling should be addressed. For example, Wnt5a antagonizes canonical Wnt/β-Catenin signaling and exhibits tumor-suppressive activity in some circumstances [ 221 , 481 483 ], but other studies have reported that Wnt5a controls both canonical and noncanonical Wnt signaling [ 15 , 16 , 484 ]. Nusse et al explained that Wnt5a activates or inhibits β-Catenin–TCF signaling depending on the receptor context [ 485 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ALKBH5 contributed to GBMSC maintenance, proliferation, and tumorigenicity by enhancing the expression of the transcription factor FOXM1 [ 14 ]. Recently, the role of ALKBH5 has been confirmed in the proliferation of GBM cell lines via the upregulation of SOX2 expression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%